На шляху до державності (До 70-річчя проголошення незалежності Карпатської України) - Цубов, Л. (Інститут політичних і етнонаціональних досліджень ім. І.Ф. Кураса НАН України, 2009)
Аналізуються передумови проголошення незалежності Карпатської України. Розглянуто особливості взаємодії та взаємовпливу різноманітних політичних сил Закарпаття в умовах багатопартійності у міжвоєнний період. Досліджено своєрідність зародження та етапи розвитку проукраїнських політичних партій краю на шляху до незалежності. On the way to the statehood (to the 70th anniversary of the independence declaration of Karpatsky Ukraine). The preconditions for the independence declaration of the Carpathian Ukraine have been analyzed. The specific features of political and mutual creation process and the stages of Transcarpathian Ukrainian parties development in the multi — party circumstances in the inter — war period have been considered. Creation peculiarities and the stages of Ukrainian political parties development in the process towards national independence have been highlighted.